P04.07 Correlation of 18F-fluorethyl-L-tyrosine (18F-FET) uptake in positron emission tomography (PET) and MRI growth rate in low-grade glioma. (6th September 2019) - Mueller, M; Kamp, M; Sabel, M; Stoffels, G; Galldiks, N; Langen, K; Rapp, M
Abstract: BACKGROUND: Low-grade gliomas (LGGs, WHO grade II) are a heterogeneous group of tumors of the central nervous system with diverse behavior in histopathology, genetics and growth patterns. Therefore, different therapeutic strategies are discussed ranging from watchful waiting to radical resection and adjuvant radio-/chemotherapy. For a better evaluation of tumor progression or malignant transformation, the O-(2- 18 F-fluoroethyl)-L-tyrosine ( 18 F-FET) uptake in PET or the tumor growth rate assessed on MRI are used depending on the neurooncological center. Here, we correlated both methods. MATERIAL AND METHODS: Inclusion criteria for this retrospective study were (1) newly diagnosed and neuropathologically confirmed low-grade glioma; (2) at least two MRIs at initial diagnosis and follow-up for calculation of the tumor growth rate (using IDS7 by Sectra AB, Sweden, 2018); (3) and an additional preoperative 18 F-FET PET scan. RESULTS: From 2008 to 2018, 34 patients were identified (mean age 39.7 years; 68% diffuse astrocytoma). The mean tumor growth rate on MRI was 0.091 cm 3 /d. The average mean 18 F-FET uptake was 1.42; the average maximum 18F-FET uptake was 2.18. The Pearson correlation coefficient between the tumor growth rate and the mean and maximum 18F-FET uptake was r=0.19, and r=0.10. In the group of diffuse astrocytomas, the mean growth rate in tumors with a mean 18 F-FET uptake of >1.5 was significantly higher than the mean growth rate of those with a mean 18 F-FET uptake of ≤1.5 (p<0.1). CONCLUSION: Data suggest that astrocytic LGGs with increased 18 F-FET uptake may show a more aggressive behaviour, with a potentially higher risk for an earlier tumor progression or malignant transformation. For further elucidation of a correlation between the tumor growth rate and the 18 F-FET uptake, larger prospective studies are needed. In the future, the combination of both methods in the management of low-grade gliomas could help to detect tumor progression as well as tumor malignization more precisely.